World health forum. - World Health Organization (Geneva, World Health Organization, 1980)
"An international journal of health development."
"An international journal of health development."
Life sciences collection
Excerpta medica
Energy information abstracts
Environment abstracts
Biological abstracts
Keywords: World health -- Periodicals; Public health -- Periodicals; Community health services -- Periodicals; Public health -- Periodicals; Health planning -- Periodicals; Developing Countries -- periodicals